Resequencing of global Tartary buckwheat accessions reveals multiple domestication events and key loci associated with agronomic traits - Kaixuan Zhang; Ming He; Yu Fan; Hui Zhao; Bin Gao; Keli Yang; Faliang Li; Yu Tang; Qiang Gao; Tao Lin; Muriel Quinet; Dagmar Janovská; et al. (Genome Biology, 2021)
Abstract Background Tartary buckwheat (Fagopyrum tataricum) is a nutritionally balanced and flavonoid-rich crop plant that has been in cultivation for 4000 years and is now grown globally. Despite its nutraceutical and agricultural value, the characterization of its genetics and its domestication history is limited. Results Here, we report a comprehensive database of Tartary buckwheat genomic variation based on whole-genome resequencing of 510 germplasms. Our analysis suggests that two independent domestication events occurred in southwestern and northern China, resulting in diverse characteristics of modern Tartary buckwheat varieties. Genome-wide association studies for important agricultural traits identify several candidate genes, including FtUFGT3 and FtAP2YT1 that significantly correlate with flavonoid accumulation and grain weight, respectively. Conclusions We describe the domestication history of Tartary buckwheat and provide a detailed resource of genomic variation to allow for genomic-assisted breeding in the improvement of elite cultivars.